Effect of Balanced Nutrition Education using The Emodemo Method on Knowledge and Attitude of Obesity Adolescents at SMA Negeri 1 Krian Sidoarjo - Firda Amalia Pratiwi; Annas Buanasita; Juliana Christyaningsih; Nur Hatijah (Journal of Nutrition Explorations, 2023)
Obesity is a condition of excessive accumulation of body fat tissue which will cause disease. Obesity can be defined as a result of overeating. This study aims to determine the effect of balanced nutrition education using the emodemo method on the knowledge and attitudes. This research is a quantitative Pre-Experimental with the type of pre-test and post-test One Group Design, data collection using questionnaires. The sample of this research is 34 respondents using Proportional Random Sampling technique. Statistical tests used the Wilcoxon Signed Runk Test to determine the effect before and after being given counseling using the emodemo method module game assembling donut rings on the level of knowledge and attitudes about balanced nutrition. The level of knowledge of obese adolescents by 8.8% increased to 85.3%. While the attitude level of obese adolescents was 82.4% increasing to 88.2%. There is an effect of balanced nutrition education using the emodemo method on the knowledge and attitudes of obese adolescents. Schools can provide healthy canteens that provide balanced nutritious meals for adolescents.